2014
DOI: 10.7860/jcdr/2014/9502.4440
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Interferon Gamma (IFN-γ) in Human Plasma with Graded Physical Activity

Abstract: Plasma IFN-γ decreases with one bout of acute moderate exercise, it decreases further with one bout of acute strenuous exercise and increases at end of one month of regular moderate exercise, which is more than baseline value. This shows that regular moderate exercise has beneficial effects on health by way of increasing plasma IFN-γ level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Similar to the increase in IL-10, the concurrent small increase of IFN-γ in both the CME and CSE exercise groups (and unchanged in the controls) seems to be beneficial, since this biomarker is considered as an anti-inflammatory cytokine in low concentrations. Regular moderate exercise (as was the case in this study) and not intense exercise has beneficial effects on health by way of increasing satisfactory plasma IFN-γ levels [57].…”
Section: Immune Markersmentioning
confidence: 61%
“…Similar to the increase in IL-10, the concurrent small increase of IFN-γ in both the CME and CSE exercise groups (and unchanged in the controls) seems to be beneficial, since this biomarker is considered as an anti-inflammatory cytokine in low concentrations. Regular moderate exercise (as was the case in this study) and not intense exercise has beneficial effects on health by way of increasing satisfactory plasma IFN-γ levels [57].…”
Section: Immune Markersmentioning
confidence: 61%
“…Regular Ex modulates another novel INF pathway, with a probable COVID-19 prevention activity. Ex is beneficial for maintaining the improvement of the immune status, associated with a rise in IFN-2 (γ) in the plasma [ 25 ]. Thus, regular moderate Ex seems to modulate its release and increase its levels to those necessary for the human body to maintain good health [ 26 ].…”
Section: Intervention Through Physical Exercise On the Immune Funcmentioning
confidence: 99%
“…Migration of CD4 + and CD8 + T cells (ex vivo) reduced to supernatants of human rhinovirus (HRV)-infected bronchial epithelial cell line 1 h after completing a 2 h of running with an intensity of 60% VO 2 max [ 51 ]. However, some T cells (CD4 + , CD8 + , and γδ T cells) with a higher migration capacity and more efficient power appear to fall during Ex recovery and may have gone into the peripheral blood earlier [ 25 ]. Concretely, Simpson et al [ 52 ] have observed T cells’ activation and proliferation after exercise.…”
Section: Intervention Through Physical Exercise On the Immune Funcmentioning
confidence: 99%
“…Work from our laboratory shows that exposure of rats to an environmental enrichment paradigm triggers release of serum-derived extracellular vesicles (EVs) that promote myelination/remyelination and reduce measures of oxidative stress [5,6]. Analogous EVs can be produced ex vivo by stimulating bone marrow-derived dendritic cell cultures with interferon gamma (IFNγ), a pro-inflammatory cytokine that is phasically increased with environmental enrichment [7].…”
Section: Introductionmentioning
confidence: 99%